Positive electrode active material, positive electrode, and rechargeable lithium battery

By using layered lithium nickel-manganese composite oxides and lithium-rich composite oxides, combined with uniform coating technology, the problems of shortage of cobalt supply and high cost in lithium batteries are solved, and positive electrode active substances with high energy density and long cycle life are achieved.

CN119905544APending Publication Date: 2025-04-29SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411499263.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-27
Filing Date
2024-10-25
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The supply of cobalt-containing positive electrode active materials used in existing lithium batteries is short of supply and is expensive, making it difficult to meet the needs of high energy density and long cycle life.

Method used

The positive electrode active material containing layered lithium nickel manganese composite oxide and lithium rich manganese composite oxide is used to improve structural stability and cycle life by adjusting the ratio of nickel and manganese and introducing a uniform coating on the surface of the particles.

Benefits of technology

Positive electrode active substances with high density, high capacity and long cycle life are achieved, which reduces production costs and exhibits excellent characteristics under high voltage and high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905544A_ABST
    Figure CN119905544A_ABST
Patent Text Reader

Abstract

Disclosed are a positive electrode active material, a positive electrode including the same, and a rechargeable lithium battery, the positive electrode active material including a first positive electrode active material including a layered lithium nickel manganese-based composite oxide and a second positive electrode active material including a lithium-rich manganese composite oxide, in which a molar ratio of lithium to a total metal not containing lithium is about 1.1 to about 3, and the manganese content is greater than or equal to about 50 mol% based on 100 mol% of the total metal containing no lithium in the lithium-rich manganese composite oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Disclosed are a positive electrode active material, a positive electrode including the same, and a rechargeable lithium battery. Background Art

[0002] Portable information devices (such as cellular phones, laptop computers, smart phones, etc.) and / or electric vehicles have used rechargeable lithium batteries with high energy density (hereinafter also referred to as density) and easy portability as driving power sources. Recently, research has been actively conducted to use rechargeable lithium batteries with high energy density as driving power sources and / or energy storage power sources for hybrid and / or electric vehicles.

[0003] Various positive electrode active materials have been studied to achieve the application of rechargeable lithium batteries. Among them, lithium nickel oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides and lithium cobalt oxides are mainly used as positive electrode active materials. However, although the use of large-size, high-capacity or high-energy-density rechargeable lithium batteries has increased recently, the supply of positive electrode active materials containing rare metal cobalt is expected to be in serious shortage. Because cobalt is expensive and there is a lack of remaining reserves, people are interested in developing positive electrode active materials that do not contain cobalt or reducing its use. Summary of the invention

[0004] Some embodiments of the present disclosure provide a positive electrode active material exhibiting high density, high capacity, and long cycle life characteristics, a positive electrode including the same, and a rechargeable lithium battery including the positive electrode.

[0005] In some embodiments, the positive electrode active material includes a first positive electrode active material comprising a layered lithium nickel manganese composite oxide and a second positive electrode active material comprising a lithium-rich manganese composite oxide, wherein the molar ratio of lithium to total metal excluding lithium is from about 1.1 to about 3, and the manganese content is greater than or equal to about 50 mol% based on 100 mol% of the total metal excluding lithium in the lithium-rich manganese composite oxide.

[0006] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material.

[0007] In some embodiments, a rechargeable lithium battery includes a positive electrode, a negative electrode, and an electrolyte.

[0008] The positive electrode active material according to some embodiments can maximize or increase the capacity while minimizing or reducing the production cost to ensure long cycle life characteristics and improve high voltage characteristics and high temperature storage characteristics. When the positive electrode active material is applied to a rechargeable lithium battery, a high initial charge / discharge capacity and efficiency can be achieved under high voltage operating conditions, a long cycle life characteristic can be achieved, and the amount of gas generated due to high voltage and high temperature operation can be effectively suppressed or reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] The accompanying drawings, together with the specification, illustrate embodiments of the presently disclosed subject matter, and, together with the description, serve to explain principles of embodiments of the presently disclosed subject matter.

[0010] Figure 1 is a cross-sectional perspective view schematically illustrating a rechargeable lithium battery according to some embodiments.

[0011] Figure 2 is a cross-sectional view schematically illustrating a rechargeable lithium battery according to some embodiments.

[0012] Figure 3-4 is a perspective view schematically illustrating a rechargeable lithium battery according to some embodiments.

[0013] Figure 5-6 : is a SEM image of large particles of the first positive electrode active material prepared in Example 1.

[0014] Figure 7-8 : is a SEM image of small particles of the first positive electrode active material prepared in Example 1.

[0015] Figure 9-10 is a SEM image of the second positive electrode active material prepared in Example 1.

[0016] Fig.11 Graph comparing the densities of the positive electrode active material layers prepared in Example 1 and Comparative Example 1.

[0017] Description of Reference Numerals

[0018] 100: Rechargeable lithium battery 10: Positive electrode

[0019] 11: Positive electrode lead lug 12: Positive electrode terminal

[0020] 20: Negative electrode 21: Negative electrode lead lug

[0021] 22: Negative electrode terminal 30: Separator

[0022] 40: electrode assembly 50: shell

[0023] 60: Sealing member 70: Electrode terminal piece

[0024] 71: Positive electrode terminal tab 72: Negative electrode terminal tab DETAILED DESCRIPTION

[0025] Hereinafter, example embodiments will be described in more detail so that those skilled in the art can easily implement them. However, the subject matter of the present disclosure may be embodied in many different forms and should not be construed as limited to the example embodiments set forth herein.

[0026] The terms used herein are only used to describe the embodiments and are not intended to limit the present disclosure. Unless the context clearly indicates otherwise, a singular expression includes a plural expression.

[0027] As used herein, "combinations thereof" means mixtures, laminates, composites, copolymers, alloys, blends, reaction products, etc. of the components.

[0028] In this document, it should be understood that terms such as "comprising", "including" or "having" are intended to indicate the presence of embodied features, quantities, steps, elements or combinations thereof, but it does not exclude the possibility of the presence or addition of one or more other features, quantities, steps, elements or combinations thereof.

[0029] In the drawings, the size (e.g., thickness) of layers, films, panels, regions, etc. may be exaggerated for clarity, and like reference numerals denote like elements throughout the specification. It will be understood that when an element (such as a layer, film, region, or substrate) is referred to as being "on" another element (such as a layer, film, region, or substrate), it may be directly on the other element (such as a layer, film, region, or substrate), or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element (such as a layer, film, region, or substrate), there are no intervening elements.

[0030] In the embodiments, the “layer” herein includes not only a shape provided on the entire surface when viewed from a plan view but also a shape provided on a partial surface.

[0031] In an embodiment, the average particle size can be measured by any suitable method commonly used in the art, for example, by a particle size analyzer and / or by a transmission electron microscope image and / or a scanning electron microscope image. In an embodiment, the average particle size value can be obtained by measuring using a dynamic light scattering method, performing data analysis, counting the number of particles in each particle size range, and calculating therefrom. Unless otherwise specified, the average particle size (D 50) may refer to the diameter of particles having a cumulative volume of 50% by volume in a particle size distribution. As used herein, when no definition is otherwise provided, the average particle size (D 50 ) means the diameter of a particle having a cumulative volume of 50 volume % in a particle size distribution obtained by randomly measuring the size (diameter or length of the major axis) of about 20 particles in a scanning electron microscope image.

[0032] In this document, “or” is not interpreted as being exclusive. For example, “A or B” is interpreted as including A, B, A+B, etc.

[0033] The term "metal" is interpreted as a concept including common metals, transition metals and metalloids (semimetals).

[0034] Positive electrode active material

[0035] In some embodiments, the positive electrode active material includes a first positive electrode active material comprising a layered lithium nickel manganese composite oxide and a second positive electrode active material comprising a lithium-rich manganese composite oxide, wherein the molar ratio of lithium to total metal excluding lithium is from about 1.1 to about 3, and the manganese content is greater than or equal to about 50 mol% based on 100 mol% of the total metal excluding lithium in the lithium-rich manganese composite oxide.

[0036] The positive electrode active material may not contain expensive cobalt or may contain a very small amount of cobalt, and contain low-cost manganese, thereby reducing the cost of the positive electrode active material, and facilitating large-scale production of the positive electrode active material, and the positive electrode active material has excellent characteristics at high voltage, realizes high-density characteristics, and increases capacity. Because these positive electrode active materials are low-cost and meet the characteristics of high capacity, high voltage and high density, when rechargeable lithium batteries using them are installed on electric vehicles or hybrid vehicles, they can ensure long-distance driving.

[0037] Based on a total of 100 wt% of the first positive electrode active material and the second positive electrode active material, the content of the first positive electrode active material may be about 60 wt% to about 95 wt%, such as about 70 wt% to about 95 wt% or about 80 wt% to about 90 wt%, and the content of the second positive electrode active material may be about 5 wt% to about 40 wt%, such as about 5 wt% to about 30 wt% or about 10 wt% to about 20 wt%. If they are mixed together in the above ratio, high capacity can be achieved while maximizing or increasing energy density.

[0038] First positive electrode active material

[0039] Since the price of rare metal cobalt has risen sharply recently, it is necessary to develop positive electrode active materials that do not contain cobalt or reduce its content. Among them, positive electrode active materials with olivine crystal structure (such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), lithium manganese phosphate (LMFP), etc.) and / or spinel crystal structure (such as lithium manganese oxide (LMO), etc.) are limited in achieving high capacity due to the small amount of lithium available in the structure. Layered nickel manganese positive electrode active materials have excellent capacity and efficiency characteristics due to the high amount of lithium available in the structure, making them suitable as materials for high-capacity batteries. However, due to the removal of cobalt, which plays a key role in the layered structure, the structural stability is reduced, the resistance (e.g., resistance) increases, and it becomes difficult to ensure long cycle life characteristics. Layered nickel manganese positive electrode active materials that do not contain cobalt may have the problem of accelerating side reactions with electrolytes under high voltage and high temperature conditions, resulting in increased gas generation and deterioration of cycle life characteristics.

[0040] Accordingly, in some embodiments, a method for improving the capacity and cycle life characteristics of the first positive electrode active material under high voltage is provided by appropriately or suitably adjusting the ratio of nickel and manganese in the lithium nickel manganese composite oxide, introducing other elements (such as aluminum) in addition to nickel and manganese, and / or introducing a uniform (or substantially uniform) coating by an appropriate or suitable coating method.

[0041] Lithium nickel manganese composite oxide

[0042] Based on 100 mol% of the total metal containing no lithium in the layered lithium nickel manganese composite oxide, the nickel content in the lithium nickel manganese composite oxide may be greater than or equal to about 60 mol%, for example, about 60 mol% to about 80 mol%, about 65 mol% to about 80 mol%, about 70 mol% to about 80 mol%, about 60 mol% to about 79 mol%, about 60 mol% to about 78 mol% or about 60 mol% to about 75 mol%. If the nickel content satisfies the above range, high capacity can be achieved even if the cobalt content is reduced, and structural stability can be increased.

[0043] Based on 100 mol% of the total metal excluding lithium in the layered lithium nickel manganese composite oxide, the manganese content may be greater than or equal to about 10 mol%, for example, about 15 mol% to about 40 mol%, about 15 mol% to about 35 mol%, about 15 mol% to about 30 mol%, or about 20 mol% to about 30 mol%. If the manganese content meets the above range, the positive electrode active material can improve structural stability while achieving high capacity.

[0044] The lithium nickel manganese composite oxide may be, for example, a lithium nickel manganese aluminum composite oxide further including aluminum in addition to nickel and manganese. When the lithium nickel manganese composite oxide includes aluminum, it is beneficial to maintain a stable layered structure even if the structure does not contain cobalt. Based on 100 mol% of the total metal containing no lithium in the layered lithium nickel manganese composite oxide, the aluminum content may be greater than 0 mol% and less than or equal to about 3 mol%, greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol%, for example, about 1 mol% to about 3 mol%, about 1 mol% to about 1.5 mol%, about 1 mol% to about 2 mol%, or about 1 mol% to about 2.5 mol%. If the aluminum content meets the above range, even if cobalt is not included, a stable layered structure can be maintained, the problem of structural collapse caused by charging and discharging can be suppressed or reduced, and the long cycle life characteristics of the positive electrode active material can be achieved.

[0045] According to some embodiments, the aluminum concentration within the particles including the lithium nickel manganese composite oxide may be uniform (or substantially uniform). In an embodiment, the foregoing means that there is no aluminum concentration gradient from the center to the surface within the particle, or the aluminum concentration outside the particle is neither higher than nor lower than the aluminum concentration inside, and the aluminum within the particle is uniformly (or substantially uniformly) distributed. The foregoing may be a structure obtained by using an aluminum raw material in the precursor generation process, and not additionally doping aluminum during the synthesis of the lithium nickel manganese composite oxide, thereby using nickel manganese aluminum hydroxide as a precursor to synthesize the composite oxide. The particle may be in the form of a secondary particle in which a plurality of primary particles are aggregated, and the aluminum content inside the primary particle may be the same or similar, regardless of the position of the primary particle. In an embodiment, if a primary particle is selected at a random position in a cross section of the secondary particle, and the aluminum content is measured inside the primary particle rather than at its interface, regardless of the position of the primary particle (e.g., whether the primary particle is close to the center of the secondary particle or close to the surface), the aluminum content may be the same / similar / uniform. In this structure, even if cobalt is absent or present in a very small amount, a stable layered structure can be maintained and aluminum byproducts and / or aluminum aggregates are not generated, thereby simultaneously improving the capacity, efficiency, and cycle life characteristics of the positive electrode active material.

[0046] The lithium nickel manganese-based composite oxide may be represented by Chemical Formula 1, for example.

[0047] Chemical formula 1

[0048] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 Xb1

[0049] In Chemical Formula 1, 0.9 ≤ a1 ≤ 1.8, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.4, 0 ≤ z1 ≤ 0.03, 0 ≤ w1 ≤ 0.3, 0.9 ≤ x1 + y1 + z1 + w1 ≤ 1.1, and 0 ≤ b1 ≤ 0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X is one or more elements selected from F, P, and S.

[0050] In Chemical Formula 1, 0.9 ≤ a1 ≤ 1.5, or 0.9 ≤ a1 ≤ 1.2. In an embodiment, Chemical Formula 1 may contain aluminum, in which case, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 ≤ z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29 may be satisfied. For example, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 < z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29 may be satisfied.

[0051] In Chemical Formula 1, for example, 0.6 ≤ x1 ≤ 0.79, 0.6 ≤ x1 ≤ 0.78, 0.6 ≤ x1 ≤ 0.75, 0.65 ≤ x1 ≤ 0.8, or 0.7 ≤ x1 ≤ 0.79; 0.1 ≤ y1 ≤ 0.35, 0.1 ≤ y1 ≤ 0.30, 0.1 ≤ y1 ≤ 0.29, 0.15 ≤ y1 ≤ 0.39, or 0.2 ≤ y1 ≤ 0.3; 0.01 ≤ z1 ≤ 0.025, 0.01 < z1 ≤ 0.02, or 0.01 < z1 ≤ 0.019; and 0 ≤ w1 ≤ 0.28, 0 ≤ w1 ≤ 0.27, 0 ≤ w1 ≤ 0.26, 0 ≤ w1 ≤ 0.25, 0 ≤ w1 ≤ 0.24, 0 ≤ w1 ≤ 0.23, 0 ≤ w1 ≤ 0.22, 0 ≤ w1 ≤ 0.21, 0 ≤ w1 ≤ 0.2, 0 ≤ w1 ≤ 0.15, 0 ≤ w1 ≤ 0.1, or 0 ≤ w1 ≤ 0.09.

[0052] For example, the lithium nickel manganese composite oxide may not include cobalt or may include a small amount of cobalt, and based on the total metal excluding lithium in 100 mol% of the layered lithium nickel manganese composite oxide, the cobalt content may be about 0 mol% to about 0.01 mol%.

[0053] Particles including the lithium nickel manganese composite oxide may be in the form of secondary particles provided by aggregating a plurality of primary particles, single particles, or a combination thereof. The secondary particles and single particles may be spherical, elliptical, polyhedral, and / or irregular in shape, and the primary particles constituting the secondary particles may be spherical, elliptical, plate-shaped, or a combination thereof.

[0054] Coating

[0055] The first positive electrode active material may include a core particle including a layered lithium nickel manganese-based composite oxide and a coating layer on a surface of the core particle and containing Al, B, Mg, Ti, V, W, Y, Zr, or a combination thereof.

[0056] When the battery is operated under high voltage or high temperature conditions, the lithium nickel manganese composite oxide is susceptible to chemical corrosion by the components in the electrolyte, and therefore may undergo many side reactions with the electrolyte, resulting in increased gas generation, thereby deteriorating the battery cycle life and safety, but these problems can be solved by introducing a coating according to some embodiments therein.

[0057] For example, the coating layer may be an Al coating layer containing Al, and may further optionally contain B, Mg, Ti, V, W, Y, Zr, etc. If the Al coating layer is introduced, the high voltage performance of the first positive electrode active material may be further improved.

[0058] Because the layered lithium nickel manganese composite oxide has a significantly different content of residual lithium on the surface of the particles, and has a variety of suitable surface properties different from oxides with different compositions (such as lithium nickel cobalt manganese composite oxides, lithium nickel cobalt aluminum composite oxides, lithium cobalt oxides, etc.), it is believed that it is impossible to provide it as a uniform and satisfactory coating in a conventional coating method. Accordingly, in some embodiments, a uniform coating can be introduced into the first positive electrode active material by the following method: (i) adding a coating raw material to an aqueous solvent to prepare a coating solution, wherein the salt is completely dissolved in a salt dissolving wet coating method, (ii) mixing the coating solution with the core particles to coat them, and (iii) removing the solvent, and then drying and heat treating the resultant. The aforementioned is a salt dissolving wet coating method and a pre-addition method, in which the coating raw material of the salt is first completely dissolved, and active material particles (ie, core particles) are added thereto. By this method, a uniform (or substantially uniform) and thin coating can be successfully provided on the surface of a layered lithium nickel manganese composite oxide.

[0059] Compared with conventional drying methods or wet methods after addition, the coating method can further increase the content of coating elements on the surface of active material particles. For example, based on 100at% of the total metal without lithium on the surface, the coating content on the surface of the first positive electrode active material measured by energy distribution-energy dispersive X-ray spectroscopy (EP-EDS) analysis can be about 5at% to about 35at%, such as about 5at% to about 30at%, about 5at% to about 25at% or about 10at% to about 20at%. Within the above content range, the coating can not only increase the resistance (e.g., resistance) of the first positive electrode active material, but also effectively improve the high voltage characteristics.

[0060] For example, the coating may be in the form of a film that continuously surrounds the surface of the core particle, for example, it may be in the form of a shell that surrounds the entire surface of the core particle. This is different from a structure in which only a portion of the surface of the core particle is locally coated. According to some embodiments, the coating may be provided to completely cover the surface of the core particle, and may be provided to be very thin and uniform (or substantially uniform) in thickness, so that the positive electrode active material does not increase resistance (e.g., resistance) or reduce capacity, improve structural stability, effectively inhibit or reduce side reactions with the electrolyte, reduce the amount of gas generated under high voltage and high temperature conditions, and achieve long cycle life characteristics.

[0061] According to the method, the thickness of the coating of the first positive electrode active material may be about 5nm to about 200nm, such as about 5nm to about 150nm, about 5nm to about 100nm, about 5nm to about 80nm, about 5nm to about 50nm or about 10nm to about 50nm. When the coating meets the above thickness range, the structural stability of the positive electrode active material can be improved without increasing resistance (e.g., resistance) or reducing capacity due to the coating, and the side reaction with the electrolyte can be effectively suppressed or reduced. The thickness of the coating can be measured by, for example, scanning electron microscopy (SEM), transmission electron microscopy (TEM), time-of-flight secondary ion mass spectrometry (TOF-SIMS), X-ray photoelectron spectroscopy (XPS) or energy dispersive X-ray spectroscopy (EDS) analysis, for example, the cross section of the positive electrode active material can be measured by transmission electron microscopy-energy dispersive X-ray spectroscopy (TEM-EDS) line profile.

[0062] According to some embodiments, the coating may be thin and uniform (or substantially uniform) in thickness, ranging from a few nanometers to several hundred nanometers, such as a few nanometers to tens of nanometers. For example, the variation in the coating thickness within a positive electrode active material particle may be less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. In an embodiment, the deviation of the coating thickness refers to the deviation of the coating thickness within a positive electrode active material particle. For example, the deviation of the coating thickness can be calculated by measuring the thickness of about 10 points in an electron microscope image of a cross section of a single positive electrode active material particle to calculate the arithmetic mean, and then dividing the absolute value of the difference between one measurement data and the arithmetic mean by the arithmetic mean and multiplying by 100. The fact that the deviation or standard deviation of the coating thickness satisfies the above range means that a coating of uniform thickness is provided in the form of a film on the surface of the positive electrode active material particle. Accordingly, the structural stability of the positive electrode active material is improved, the side reaction with the electrolyte is effectively suppressed or reduced, and the increase in resistance (e.g., resistance) and / or the decrease in capacity due to the coating can be minimized or reduced.

[0063] The content of the coating element may vary depending on the type (or species) of the coating element, but based on 100 mol% of the total metal excluding lithium in the entire first positive electrode active material, the content of the coating element may be about 0.01 mol% to about 5 mol%, for example, about 0.05 mol% to about 3 mol% or about 0.1 mol% to about 2 mol%.

[0064] For example, if an Al coating is introduced, the Al content of the coating may be about 0.1 mol% to about 3.0 mol%, e.g., about 0.1 mol% to about 2.0 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.7 mol% to about 1.3 mol%, based on 100 mol% of the total metal excluding lithium in the entire first positive electrode active material.

[0065] If an Al coating is introduced, the coating may include, for example, a layered aluminum compound (such as aluminum oxide), a lithium aluminum oxide (such as LiAlO2), or a combination thereof.

[0066] Large and small particles

[0067] In some embodiments, the first positive electrode active material may include a layered lithium nickel manganese composite oxide having an average particle size (D 50 ) is about 10 μm to about 25 μm and contains layered lithium nickel manganese composite oxides and an average particle size (D 50 ) is about 0.5 μm to about 8 μm. In an embodiment, a positive electrode with a high energy density can be achieved. As used herein, when not otherwise defined, the average particle size (D 50 ) means the diameter of a particle having a cumulative volume of 50% by volume in a particle size distribution obtained by randomly measuring the sizes (diameters or major axis lengths) of about 20 particles in a scanning electron microscope image of a positive electrode active material.

[0068] The large particle may be in the form of a secondary particle provided by aggregating a plurality of primary particles. The small particle may be in the form of a secondary particle or a single particle.

[0069] Based on 100 wt % of the total of large particles and small particles, the content of large particles may be about 60 wt % to about 95 wt % or about 70 wt % to about 90 wt %, and the content of small particles may be about 5 wt % to about 40 wt % or about 10 wt % to about 30 wt %.

[0070] If the first positive electrode active material includes large particles and small particles, based on a total of 100 wt % of the large particles, the small particles and the second positive electrode active material, the content of the large particles may be about 40 wt % to about 90 wt %, the content of the small particles may be about 5 wt % to about 40 wt %, and the content of the second positive electrode active material may be about 5 wt % to about 30 wt %.

[0071] If the above mixing ratio is met, the energy density and capacity can be maximized.

[0072] For example, the average particle size (D 50 ) can be smaller than the average particle size of large particles (D 50 ) and is larger than the average particle size of the small particles (D 50 ). In an embodiment, the second positive electrode active material becomes a medium-sized type (or kind) of particles, and the positive electrode can be a mixture of large particles, medium-sized particles, and small particles, thereby maximizing or increasing energy density and effectively improving high voltage characteristics.

[0073] In some embodiments, the large particle may include a core particle in the form of a secondary particle provided by aggregating a plurality of primary particles and a coating on the surface of the core particle of the large particle and containing Al, B, Mg, Ti, V, W, Y, Zr or a combination thereof. In an embodiment, the small particle may include a core particle in the form of a single particle and a coating on the surface of the core particle of the small particle and containing Al, B, Mg, Ti, V, W, Y, Zr or a combination thereof. In an embodiment, the performance at high voltage may be maximized or increased.

[0074] For example, the coating of large particles may include Al, Zr or a combination thereof, and the coating of small particles may include Al, Y or a combination thereof. This may be an appropriate or optimal coating component for large and small particles, and may further improve the capacity characteristics and cycle life characteristics at high voltages.

[0075] For example, the coating of the large particles may include Al, and the Al content of the coating of the large particles may be about 0.5 mol% to about 2 mol% based on 100 mol% of the total metal excluding lithium in the large particles. In an embodiment, the coating of the small particles may include Al, and the Al content of the coating of the small particles may be about 0.1 mol% to about 1 mol% based on 100 mol% of the total metal excluding lithium in the small particles.

[0076] In an embodiment, the coating layer of the small particle may further include Y, and the Y content of the coating layer of the small particle may be, for example, about 0.01 mol % to about 0.5 mol % based on 100 mol % of total metal excluding lithium in the small particle.

[0077] In an embodiment, the first positive electrode active material may include a sulfur (S) component on the surface, and this may be a characteristic obtained by applying a sulfate-based coating material such as aluminum sulfate during a coating process.

[0078] Second positive electrode active material

[0079] The second positive electrode active material includes a lithium-rich manganese (LMR) composite oxide. LMR materials (which are layered positive electrode active materials containing an excessive amount of lithium and a relatively high amount of manganese) can not only improve capacity through conventional redox of transition metals, but also achieve high capacity by applying a new principle of redox of oxygen, while (e.g., simultaneously) attracting attention as ultra-low-cost next-generation positive electrode active materials by containing low-cost manganese at a high ratio.

[0080] In the second positive electrode active material, the molar ratio of lithium based on the total metal excluding lithium may be about 1.1 to about 3, such as about 1.2 to about 2.5, about 1.3 to about 2.3, or about 1.5 to about 2.1. In an embodiment, the manganese content may be greater than or equal to about 60 mol%, such as about 60 mol% to about 90 mol%, about 60 mol% to about 80 mol%, about 60 mol% to about 75 mol%, about 60 mol% to about 70 mol%, or about 62 mol% to about 68 mol%, based on 100 mol% of the total metal excluding lithium in the lithium-rich manganese composite oxide.

[0081] The lithium-rich manganese composite oxide of the second positive electrode active material may be represented by Chemical Formula 2, for example.

[0082] Chemical formula 2

[0083] Li 1+x2 (Ni y2 Mn z2 M 2 1-y2-z2 ) 1-x2 O 2-b2 X b2

[0084] In Chemical Formula 2, 0.04≤x2≤0.5, 0.1≤y2≤0.5, 0.5≤z2≤0.9, and 0≤b2≤0.1, M 2 is one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more elements selected from F, P and S.

[0085] In Chemical Formula 2, for example, 0.05≤x2≤0.4 or 0.06≤x2≤0.3, and 0.2≤y2≤0.4 and 0.6≤z2≤0.8, or 0.3≤y2≤0.4 and 0.6≤z2≤0.7.

[0086] The second positive electrode active material may be in the form of secondary particles provided by aggregating a plurality of primary particles, and the average particle size (D 50 ) may be about 3 μm to about 13 μm, for example, about 4 μm to about 12 μm, 5 μm to about 10 μm, or 6 μm to about 9 μm.

[0087] The cobalt content may be about 0 mol % to about 0.01 mol % based on 100 mol % of total metal excluding lithium in the lithium-rich manganese composite oxide of the second positive electrode active material.

[0088] The second positive electrode active material may have a X-ray diffraction analysis (XRD) of greater than or equal to about (For example, greater than or equal to about or about ~Approx. ). For example, the positive electrode active material may have a lattice constant greater than or equal to about In an embodiment, the ratio of the c lattice constant to the a lattice constant may be less than or equal to about 4.968, for example, less than or equal to about 4.965, less than or equal to about 4.960, or may be about 4.955 to about 4.965. If the ratio of the c lattice constant to the a lattice constant of the positive electrode active material satisfies the above range, the voltage drop problem during charging and discharging according to the second positive electrode active material can be effectively improved, and in addition, the energy density can be increased, and the capacity characteristics and cycle life characteristics in the high voltage region can be improved.

[0089] The second positive electrode active material may have a residual lithium content of less than or equal to about 0.3 wt % (e.g., less than or equal to about 0.2 wt %, less than or equal to about 0.1 wt % or about 0.001 wt % to about 0.1 wt %) on the surface based on 100 wt % of the second positive electrode active material. This may be a feature that distinguishes the positive electrode active material according to some embodiments from a high nickel-based material having a nickel content greater than about 70 mol %.

[0090] Powder compaction density

[0091] According to some embodiments, the positive electrode active material can achieve a high pellet density. For example, the pellet density of the positive electrode active material can be about 3.0 g / cc to about 3.7 g / cc, such as about 3.1 g / cc to about 3.6 g / cc or about 3.1 g / cc to about 3.5 g / cc. Rechargeable lithium batteries using these positive electrode active materials can achieve high energy density.

[0092] The powder compaction density can be measured in the following manner.

[0093] Weigh 3 g of the positive electrode active material and put it into a mold (area: about 1.298 cm 2 ), the mold rod is slowly inserted into the mold body. Subsequently, the mold set is placed in a hydraulic press and pressed for about 30 seconds at a pressure of about 4 tons (metric tons) to measure the height, which is used to obtain the powder compaction density.

[0094] Positive electrode

[0095] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material. In addition to the above-mentioned positive electrode active material, the positive electrode active material layer may further include other types (or types) of positive electrode active materials. In an embodiment, the positive electrode active material layer may optionally further include a binder, a conductive material (e.g., a conductive material) or a combination thereof.

[0096] According to some embodiments, the loading level of the positive electrode active material layer may be about 10 mg / cm 2 ~ about 40mg / cm 2 , for example about 10 mg / cm 2 ~about 30mg / cm 2 or about 10 mg / cm 2 ~about 20mg / cm 2 . In an embodiment, the density of the positive electrode active material layer in the final pressed positive electrode may be about 3.3 g / cc to about 3.7 g / cc, for example, about 3.3 g / cc to about 3.6 g / cc, about 3.4 g / cc to about 3.58 g / cc, or about 3.5 g / cc to about 3.58 g / cc. When applying the positive electrode active material according to some embodiments, it is beneficial or advantageous to implement such a loading level and positive electrode density, and a positive electrode satisfying the loading level and positive electrode density within the above range is suitable for realizing a high capacity, high energy density rechargeable lithium battery.

[0097] Binder

[0098] The binder improves the bonding properties between the positive electrode active material particles and the bonding properties between the positive electrode active material particles and the positive electrode current collector. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth) acrylated styrene-butadiene rubber, epoxy resin, (meth) acrylic resin, polyester resin and / or nylon, but are not limited thereto.

[0099] Conductive Materials

[0100] The conductive material is included to provide electrode conductivity (e.g., electrical conductivity), and any suitable conductive material may be used as the conductive material unless it causes chemical changes (e.g., undesirable chemical changes in a rechargeable lithium battery). Examples of the conductive material may include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powders and / or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers (e.g., conductive polymers) such as polyphenylene derivatives; or mixtures thereof.

[0101] The binder and the conductive material may each be included in an amount of about 0.5 wt % to about 5 wt % based on 100 wt % of the positive electrode active material layer.

[0102] The positive electrode current collector may include Al, but is not limited thereto.

[0103] Rechargeable lithium battery

[0104] Some embodiments provide a rechargeable lithium battery including the aforementioned positive electrode, negative electrode, and electrolyte. As an example, the rechargeable lithium battery may include a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte solution.

[0105] According to the shape, the rechargeable lithium batteries can be classified into cylindrical, prismatic, pouch, coin, etc. Figure 1 to Figure 4 is a schematic diagram showing a rechargeable lithium battery according to some embodiments, wherein Figure 1 For cylindrical batteries, Figure 2 is a prismatic cell, and Figure 3-4 Each is a pouch-shaped battery. Figure 1 to Figure 4 , the rechargeable lithium battery 100 includes an electrode assembly 40 (which has a separator 30 interposed between a positive electrode 10 and a negative electrode 20) and a case 50 (in which the electrode assembly 40 is housed). The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte solution. The rechargeable lithium battery 100 may include a sealing member 60 that seals the case 50, such as Figure 1 As shown in Figure 2 In the embodiment, the rechargeable lithium battery 100 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. Figure 3-4 As shown in FIG. 1 , the rechargeable lithium battery 100 includes an electrode tab 70 ( Figure 4 ), for example, a positive electrode terminal tab 71 and a negative electrode terminal tab 72 ( Figure 3 ).

[0106] A rechargeable lithium battery according to some embodiments may be rechargeable at a high voltage, or may be suitable for driving at a high voltage, and may be a battery having improved characteristics at a high voltage.

[0107] In a rechargeable lithium battery including a lithium-rich manganese material as a second positive electrode active material, in order to use the reversible positive electrode capacity of the second positive electrode active material, the initial charge should be performed at a voltage of about 4.60V or higher (e.g., about 4.65V). Subsequent charging is performed in a voltage range lower than the initial charging voltage, but because the rechargeable lithium battery according to some embodiments is designed to be driven in a high voltage region, the charging can be performed in a voltage range of about 4.45V or higher. For example, the charging voltage of the rechargeable lithium battery after the second charge and discharge cycle may be greater than or equal to about 4.45V, may be about 4.45V to about 4.7V, about 4.45V to about 4.6V, or about 4.45V to about 4.55V. By applying the positive electrode active material according to some embodiments, the rechargeable lithium battery can significantly reduce the amount of gas generated even when charged at a high voltage, and can achieve high capacity and long cycle life characteristics.

[0108] Negative electrode

[0109] The negative electrode may include a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, and may further include a negative electrode active material, a binder, a conductive material (eg, an electrically conductive material), or a combination thereof.

[0110] Negative electrode active material

[0111] The negative electrode active material may include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, and / or a transition metal oxide.

[0112] The material that reversibly intercalates / deintercalates lithium ions may include, for example, crystalline carbon, amorphous carbon, or a combination thereof as a carbonaceous negative electrode active material. The crystalline carbon may be amorphous and / or flaky, sheet-like, spherical, and / or fibrous natural graphite and / or artificial graphite. The amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization product, calcined coke, etc.

[0113] The lithium metal alloy includes an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0114] The material capable of doping / dedoping lithium can be a Si-based negative electrode active material and / or a Sn-based negative electrode active material. The Si-based negative electrode active material can include silicon, a silicon-carbon composite, SiO x (0 < x ≤ 2), a Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, such as Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof) or a combination thereof. The Sn-based negative electrode active material can be Sn, SnO2, a Sn alloy, or a combination thereof.

[0115] The silicon-carbon composite can be a composite of silicon and amorphous carbon. The average particle size (D 50 ) of the silicon-carbon composite particles can be, for example, about 0.5 μm to about 20 μm. According to some embodiments, the silicon-carbon composite can be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, it can include secondary particles (cores) in which silicon primary particles are aggregated and an amorphous carbon coating (shell) on the surface of the secondary particles. Amorphous carbon can also be present between the silicon primary particles. For example, the silicon primary particles can be coated with amorphous carbon. The secondary particles can be dispersed in an amorphous carbon matrix.

[0116] The silicon-carbon composite can further include crystalline carbon. For example, the silicon-carbon composite can include a core containing crystalline carbon and silicon particles and an amorphous carbon coating on the surface of the core. The crystalline carbon can be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon can include soft carbon and / or hard carbon, mesophase pitch carbonized products, and / or calcined coke.

[0117] When the silicon-carbon composite includes silicon and amorphous carbon, based on 100 wt% of the silicon-carbon composite, the content of silicon can be about 10 wt% to about 50 wt% and the content of amorphous carbon can be about 50 wt% to about 90 wt%. In an embodiment, when the silicon-carbon composite includes silicon, amorphous carbon, and crystalline carbon, based on 100 wt% of the silicon-carbon composite, the content of silicon can be about 10 wt% to about 50 wt%, the content of crystalline carbon can be about 10 wt% to about 70 wt%, and the content of amorphous carbon can be about 20 wt% to about 40 wt%.

[0118] In an embodiment, the thickness of the amorphous carbon coating can be about 5 nm to about 100 nm. The average particle size (D 50 ) of the silicon particles (primary particles) can be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles can exist in the form of elemental silicon, silicon alloys, and / or oxidized forms of silicon. The oxidized form of silicon can be represented by SiO x (0 < x ≤ 2). In this document, the atomic content ratio of Si:O indicating the degree of oxidation can be about 99:1 to about 33:67. As used herein, when not otherwise limited, the average particle size (D 50 ) indicates the diameter of the particles in which the cumulative volume in the particle size distribution is about 50 vol%.

[0119] Si-based negative electrode active materials and / or Sn-based negative electrode active materials can be mixed with carbon-based negative electrode active materials. When the Si-based negative electrode active materials and / or Sn-based negative electrode active materials are mixed with the carbon-based negative electrode active materials and used, the mixing ratio can be a weight ratio of about 1:99 to about 90:10.

[0120] Binder

[0121] The binder is used to well bond the negative electrode active material particles to each other and is also used to bond the negative electrode active material to the negative electrode current collector. The binder can be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.

[0122] The non-aqueous binder can include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0123] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenol resin, epoxy resin, polyvinyl alcohol or a combination thereof.

[0124] When the aqueous binder is used as a binder in the negative electrode active material layer, a cellulose compound capable of imparting or increasing viscosity may be further included. As the cellulose compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose and alkali metal salts thereof may be mixed and used. The alkali metal may be Na, K and / or Li.

[0125] The dry binder may be a polymer material capable of becoming fibers (eg, capable of fiberization), and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.

[0126] Conductive Materials

[0127] The conductive material is included to provide electrode conductivity (e.g., electrical conductivity), and any suitable conductive material can be used as the conductive material unless it causes chemical changes (e.g., undesirable chemical changes in a rechargeable lithium battery). Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powders and / or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers (e.g., conductive polymers) such as polyphenylene derivatives; or mixtures thereof.

[0128] Based on 100wt% of the negative electrode active material layer, the content of the negative electrode active material may be about 95wt% to about 99.5wt%, and based on 100wt% of the negative electrode active material layer, the content of the binder may be about 0.5wt% to about 5wt%. For example, the negative electrode active material layer may include about 90wt% to about 99wt% of the negative electrode active material, about 0.5wt% to about 5wt% of the binder, and about 0.5wt% to about 5wt% of the conductive material.

[0129] Negative current collector

[0130] The negative electrode current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) and / or alloys thereof, and may be in the form of foil, sheet and / or foam. The thickness of the negative electrode current collector may be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 7 μm to about 10 μm.

[0131] Electrolytes

[0132] For example, the electrolyte for a rechargeable lithium battery may be an electrolyte solution that may include a non-aqueous organic solvent and a lithium salt.

[0133] The non-aqueous organic solvent is used as a medium for transmitting ions participating in the electrochemical reaction of the battery. The non-aqueous organic solvent may include a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, an alcohol solvent, an aprotic solvent, or a combination thereof.

[0134] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valerolactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. In an embodiment, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles (such as R-CN, where R is a C2-C20 straight chain, branched or cyclic hydrocarbon group, and may include double bonds, aromatic rings and / or ether bonds, etc.); amides (such as dimethylformamide); dioxolanes (such as 1,3-dioxolane, 1,4-dioxolane, etc.); cyclopentane sulfone, etc.

[0135] The non-aqueous organic solvent may be used alone or in a mixture of two or more types (or species), and when two or more types (or species) are used in a mixture, the mixing ratio may be appropriately or suitably adjusted according to appropriate or desired battery performance, which should be apparent to those skilled in the art upon reading this disclosure.

[0136] When the carbonate-based solvent is used, the cyclic carbonate and the chain carbonate may be mixed together and used, and the cyclic carbonate and the chain carbonate may be mixed together in a volume ratio of about 1:1 to about 1:9.

[0137] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, a carbonate-based solvent and an aromatic hydrocarbon organic solvent may be mixed together and used in a volume ratio of about 1:1 to about 30:1.

[0138] The electrolyte solution may further include vinyl ethylene carbonate, vinylene carbonate and / or ethylene carbonate-based compounds to improve the battery cycle life.

[0139] Examples of the ethylene carbonate-based compound may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.

[0140] The lithium salt dissolved in the non-aqueous organic solvent supplies lithium ions in the battery, enables the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts may include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are integers of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFBOP) and lithium bis(oxalato)borate (LiBOB).

[0141] The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. If the concentration of the lithium salt is within the above range, the electrolyte solution has appropriate or suitable ion conductivity and viscosity, and thus excellent performance may be achieved, and lithium ions may be efficiently moved.

[0142] Diaphragm

[0143] Depending on the type (or kind) of the rechargeable lithium battery, there may be a separator between the positive electrode and the negative electrode. The separator may include a polyethylene separator, a polypropylene separator, a polyvinylidene fluoride separator, or a multilayer film of two or more layers thereof (such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, and / or a polypropylene / polyethylene / polypropylene three-layer separator, etc.).

[0144] The separator may include a porous substrate and a coating on one or both surfaces of the porous substrate, the coating including an organic material, an inorganic material, or a combination thereof.

[0145] The porous substrate may be a polymer film comprising any one polymer selected from polyolefins (such as polyethylene and polypropylene), polyesters (such as polyethylene terephthalate and polybutylene terephthalate), polyacetals, polyamides, polyimides, polycarbonates, polyetherketones, polyaryletherketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene oxides, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fibers, and polytetrafluoroethylene (e.g., Teflon), or copolymers or mixtures of two or more thereof.

[0146] The porous substrate may have a thickness of about 1 μm to about 40 μm (eg, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm).

[0147] The organic material may include a (meth)acryl-based copolymer including a first structural unit derived from (meth)acrylamide, and a second structural unit including at least one of a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamide sulfonic acid or a salt thereof.

[0148] The inorganic material may include inorganic particles selected from the group consisting of Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof, but is not limited thereto. The average particle size (D 50 ) may be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.

[0149] The organic material and the inorganic material may be mixed together in one coating layer, or a coating layer including an organic material and a coating layer including an inorganic material may be stacked.

[0150] The coating layer may have a thickness of about 0.5 μm to about 20 μm, for example, about 1 μm to about 10 μm or about 1 μm to about 5 μm.

[0151] Examples and comparative examples of the present disclosure are described below. However, the following examples are merely exemplary embodiments of the present disclosure, and the present disclosure is not limited to the following examples.

[0152] Example 1

[0153] 1. Preparation of positive electrode active material

[0154] (1) Preparation of large particles of the first positive electrode active material

[0155] By 0.75 Mn0.23 Al 0.02 (OH)2 and LiOH were mixed together in a molar ratio of 1:1.05, and the mixture was heat-treated at 850°C for 8 hours in an oxygen atmosphere to prepare a molten-liquid phase having an average particle size (D 50 ) in the form of secondary particles of about 14 μm, with a composition of Li 1.05 Ni 0.75 Mn 0.23 Al 0.02 The first lithium nickel manganese composite oxide of O2.

[0156] A coating solution is prepared by adding aluminum sulfate to a distilled water solvent and then stirring the mixture at about 350rpm for about 5 minutes. Check whether the coating solution is colorless and transparent and whether the salt is completely dissolved. Subsequently, 500g of the first lithium nickel manganese composite oxide is added to the coating solution while continuously stirring for 15 minutes and then further stirring for about 45 minutes. The aluminum content in the aluminum sulfate is designed to be 1.0mol% based on the total metal content of lithium-free in the final large particles of 100mol%. When stirring is completed, the pH value of its supernatant is 5.5. After removing the solvent from the mixed solution using an aspirator and a filter press, the resultant is vacuum dried at 190°C to obtain a coated product.

[0157] The coated product was subjected to secondary heat treatment at 850° C. for 8 hours under an oxygen atmosphere to prepare large particles in the first positive electrode active material.

[0158] Figure 5-6 The SEM image of large particles.

[0159] (2) Preparation of small particles of the first positive electrode active material

[0160] By 0.75 Mn 0.23 Al 0.02 (OH)2, LiOH and Al2O3 were mixed together in a molar ratio of 1:1:0.02, and then the mixture was heat-treated at 850°C for 8 hours in an oxygen atmosphere to prepare a molten-salt mixture with an average particle size (D 50 ) in the form of individual particles of about 3 μm, with a composition of LiNi 0.75 Mn 0.23 Al 0.02 The second lithium nickel manganese composite oxide of O2.

[0161] After adding aluminum sulfate and yttrium nitrate to a distilled water solvent and mixing them, a second lithium nickel manganese composite oxide is added thereto, and then mixed together for 45 minutes. Based on 100 mol% of the total metal content of the final small particles without lithium, the aluminum content of aluminum sulfate and the yttrium content of yttrium nitrate are designed to be 0.4 mol% and 0.05 mol%, respectively. After removing the solvent from the solution, the resultant is dried at 190°C, and then, a secondary heat treatment is performed at 825°C for 8 hours in an oxygen atmosphere to prepare small particles in the first positive electrode active material.

[0162] Figure 7-8 The SEM image of the prepared small particles.

[0163] (3) Preparation of the Second Positive Electrode Active Material

[0164] Ni 0.35 Mn 0.65 (OH)2 and LiOH were mixed together to have a Li / (Ni+Mn) molar ratio of about 2.1, and then heat-treated at 950°C for 24 hours in an oxygen atmosphere to prepare a quartz crystal with an average particle size (D 50 ) in the form of secondary particles of about 8 μm including lithium-rich manganese composite oxide (Li 1.35 (Ni 0.35 Mn 0.65 ) 0.65 O2) as a second positive electrode active material.

[0165] Figure 9-10 is a SEM image of the second positive electrode active material.

[0166] (4) Preparation of the final positive electrode active material

[0167] 70 wt% of the large particles of the first positive electrode active material, 20 wt% of the small particles of the first positive electrode active material, and 10 wt% of the second positive electrode active material were mixed together to obtain a final positive electrode active material. The final positive electrode active material was pressed at a pressure of 4 tons for 30 seconds to measure the powder compaction density, which was about 3.47 g / cc.

[0168] 2. Manufacturing of rechargeable lithium battery cells

[0169] 98.5 wt % of a positive electrode active material, 1.0 wt % of a polyvinylidene fluoride binder, and 0.5 wt % of a carbon nanotube conductive material were mixed together to prepare a positive electrode active material layer slurry, and the slurry was coated on an aluminum foil current collector, then dried and pressed to manufacture a positive electrode.

[0170] 97.5 wt% of graphite negative electrode active material, 1.5 wt% of carboxymethyl cellulose and 1 wt% of styrene-butadiene rubber were mixed together in an aqueous solvent to prepare a negative electrode active material layer slurry. The negative electrode active material layer slurry was coated on a copper foil current collector, then dried and compressed to make a negative electrode.

[0171] A rechargeable lithium battery cell was manufactured in a conventional method using a polytetrafluoroethylene separator and using an electrolyte solution prepared by dissolving 1M LiPF6 in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7.

[0172] Example 2

[0173] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that 90 wt % of large particles of the first positive electrode active material and 10 wt % of the second positive electrode active material were mixed together to prepare a final positive electrode active material.

[0174] The final positive electrode active material of Example 2 had a powder compaction density of about 3.10 g / cc.

[0175] Comparative Example 1

[0176] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that 70 wt % of large particles of the first positive electrode active material and 30 wt % of small particles of the first positive electrode active material were mixed together to prepare a final positive electrode active material.

[0177] Comparative Example 2

[0178] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that separate large particles of the first positive electrode active material were used to prepare the final positive electrode active material.

[0179] Comparative Example 3

[0180] A positive electrode active material and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that separate small particles of the first positive electrode active material were used to prepare the final positive electrode active material.

[0181] Evaluation Example 1: Density of positive electrode active material layer

[0182] The density according to the compressive strength (ie, pressure interval) of the positive electrode active material layer according to Example 1 and Comparative Example 1 was measured, and the results were Fig.11 Reference Fig.11The compressed positive electrode of Example 1 showed a density of 3.52 g / cc, while the compressed positive electrode active material layer of Comparative Example 1 showed a density of 3.47 g / cc, confirming that Example 1 achieved a higher density than Comparative Example 1.

[0183] Evaluation Example 2: Evaluation of Battery Performance

[0184] The rechargeable lithium battery cells of Examples 1 and 2 in which the lithium-rich manganese material is applied as the second positive electrode active material are initially charged at 4.65V and then continue to charge by reducing the voltage to 4.45V. In other words, at 25°C, the rechargeable lithium battery cells of Examples 1 and 2 are charged to 4.65V at a constant current of 0.1C, maintained at the same voltage until the current is reduced to 0.05C, and discharged to 2.5V at a constant current of 0.1C for the first charge and discharge. Subsequently, at 25°C, the rechargeable lithium battery cells are charged to 4.45V at a constant current of 0.2C, maintained at the same voltage until the current becomes 0.05C, and then discharged to 2.5V at a constant current of 0.2C for the second charge and discharge to measure the second discharge capacity. In Table 1, the second discharge capacity is shown as "first 4.65V and second 4.45V capacity".

[0185] Subsequently, at 45°C, in the voltage range of 3.0V to 4.45V, the rechargeable lithium battery cell was charged and discharged at 1.0C for 50 cycles or more to measure the 50th cycle discharge capacity, which was used to calculate the ratio of the 50th cycle discharge capacity to the second discharge capacity, and the results are shown in Table 1 as "4.45V cycle life".

[0186] Respectively, at 25° C., the rechargeable lithium battery cells of Comparative Examples 1 to 3 were charged to an upper voltage limit of 4.45V at a constant current of 0.2C, charged to 0.05C at a constant voltage, and discharged to a cutoff voltage of 3.0V at 0.2C to perform initial charging and discharging to measure the initial discharge capacity. In Table 1, the initial discharge capacity is shown as "4.45V capacity".

[0187] Subsequently, at 45°C, in the voltage range of 3.0V to 4.45V, the rechargeable lithium battery cell was charged and discharged at 1.0C for 50 cycles or more to measure the 50th cycle discharge capacity, which was used to calculate the ratio of the 50th cycle discharge capacity to the initial discharge capacity, and the results are shown as "4.45V cycle life" in Table 1.

[0188] Table 1

[0189]

[0190] Referring to Table 1, Example 1 and Example 2 exhibited improved utilization of the positive electrode and improved cycle-life characteristics compared to the comparative example.

[0191] Although the subject matter of the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it is to be understood that the present disclosure is not limited to the disclosed embodiments. Instead, the present disclosure is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the claims and their equivalents.

Claims

1. A positive electrode active material comprising: The first positive electrode active material comprises a layered lithium nickel manganese composite oxide; and The second positive electrode active material comprises a lithium-rich manganese composite oxide, wherein the molar ratio of lithium to total metal excluding lithium is 1.1 to 3, and the manganese content is greater than or equal to 50 mol% based on 100 mol% of the total metal excluding lithium in the lithium-rich manganese composite oxide.

2. The positive electrode active material according to claim 1, wherein: The first positive electrode active material may include 60 wt % to 95 wt % and the second positive electrode active material may include 5 wt % to 40 wt % based on 100 wt % of the first positive electrode material and the second positive electrode active material.

3. The positive electrode active material according to claim 1, wherein: The layered lithium nickel manganese based composite oxide of the first positive electrode active material has a nickel content of greater than or equal to 60 mol % and a manganese content of greater than or equal to 10 mol % based on 100 mol % of total metal excluding lithium in the layered lithium nickel manganese based composite oxide.

4. The positive electrode active material according to claim 1, wherein: The layered lithium nickel manganese composite oxide further comprises aluminum, and the aluminum content is greater than 0 mol % and less than or equal to 3 mol %, based on 100 mol % of the total metal excluding lithium in the layered lithium nickel manganese composite oxide, and optionally, The concentration of aluminum in the layered lithium nickel manganese-based composite oxide of the first positive electrode active material is uniform.

5. The positive electrode active material according to claim 1, wherein: Based on 100 mol % of the total metal excluding lithium in the layered lithium nickel manganese composite oxide, the cobalt content is 0 mol % to 0.01 mol %, and / or The cobalt content is 0 mol % to 0.01 mol % based on 100 mol % of the total metal excluding lithium in the lithium-rich manganese composite oxide of the second positive electrode active material.

6. The positive electrode active material according to claim 1, wherein: The layered lithium nickel manganese composite oxide of the first positive electrode active material is represented by Chemical Formula 1: Chemical formula 1 Li a1 Ni x1 Mr y1 Al z1 M 1 w1 O 2-b1 X b1 Wherein in Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more elements selected from F, P and S, and The lithium-rich manganese composite oxide of the second positive electrode active material is represented by Chemical Formula 2: Chemical formula 2 Li 1+x2 (Ni y2 Mr z2 M 2 1-y2-z2 ) 1-x2 O 2-b2 X b2 Wherein, in Chemical Formula 2, 0.04≤x2≤0.5, 0.1≤y2≤0.5, 0.5≤z2≤0.9, and 0≤b2≤0.1, M 2 is one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more elements selected from F, P and S.

7. The positive electrode active material according to claim 1, wherein: The first positive electrode active material includes core particles containing the layered lithium nickel manganese composite oxide, and A coating is on the surface of the core particle and includes Al, B, Mg, Ti, V, W, Y, Zr or a combination thereof.

8. The positive electrode active material according to claim 7, wherein: The coating layer includes Al and is in the form of a shell continuously surrounding the surface of the core particle.

9. The positive electrode active material according to claim 7, wherein: The thickness of the coating is 5nm to 200nm, and / or The coating layer may contain the coating element in an amount of 0.01 mol % to 5 mol % based on 100 mol % of total metal excluding lithium in the first positive electrode active material.

10. The positive electrode active material according to claim 1, wherein: The first positive electrode active material includes large particles containing the layered lithium nickel manganese composite oxide and having an average particle size of 10 μm to 25 μm and / or small particles containing the layered lithium nickel manganese composite oxide and having an average particle size of 0.5 μm to 8 μm, wherein: The large particles are in the form of secondary particles provided by aggregating a plurality of primary particles, and The small particles are in the form of individual particles.

11. The positive electrode active material according to claim 10, wherein: The first positive electrode active material includes the large particles and the small particles, and The content of the large particles is 60 wt % to 95 wt % and the content of the small particles is 5 wt % to 40 wt % based on 100 wt % in total of the large particles and the small particles.

12. The positive electrode active material according to claim 10, wherein: The first positive electrode active material includes the large particles and the small particles, and Based on 100 wt % in total of the large particles, the small particles and the second positive electrode active material, The content of the large particles is 40wt% to 90wt%, The content of the small particles is 5wt% to 40wt%, and The content of the second positive electrode active material is 5wt% to 30wt%; and / or The average particle size of the second positive electrode active material is smaller than the average particle size of the large particles and larger than the average particle size of the small particles.

13. The positive electrode active material according to claim 10, wherein: The large particle includes a core particle in the form of a secondary particle provided by aggregating a plurality of primary particles, and a coating layer on a surface of the core particle of the large particle and including Al, B, Mg, Ti, V, W, Y, Zr or a combination thereof, and The small particles include a core particle in the form of a single particle, and a coating layer on the surface of the core particle of the small particles and including Al, B, Mg, Ti, V, W, Y, Zr or a combination thereof.

14. The positive electrode active material according to claim 13, wherein: The coating of the large particles comprises Al, Zr or a combination thereof, and The coating of the small particles includes Al, Y or a combination thereof.

15. The positive electrode active material according to claim 13, wherein: The coating of the large particle includes Al, and the Al content of the coating of the large particle is 0.5 mol% to 2 mol% based on 100 mol% of the total metal excluding lithium in the large particle, and The coating of the small particle includes Al, and the Al content of the coating of the small particle is 0.1 mol% to 1 mol% based on 100 mol% of the total metal in the small particle excluding lithium, and The coating layer of the small particle further includes Y, and the Y content of the coating layer of the small particle is 0.01 mol% to 0.5 mol% based on 100 mol% of total metals excluding lithium in the small particle.

16. The positive electrode active material according to claim 1, wherein: The second positive electrode active material is in the form of secondary particles provided by aggregating a plurality of primary particles, and / or The average particle size of the second positive electrode active material is 3 μm to 13 μm, and / or The powder compaction density of the positive electrode active material is 3.0 g / cc to 3.7 g / cc.

17. A positive electrode comprising: a positive electrode current collector, and a positive electrode active material layer on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 16.

18. The positive electrode of claim 17, wherein: The positive electrode active material layer has a density of 3.3 g / cc to 3.7 g / cc.

19. A rechargeable lithium battery comprising: The positive electrode according to claim 17 or 18, negative electrode, and Electrolytes.

20. The rechargeable lithium battery of claim 19, wherein: The initial charging voltage is greater than or equal to 4.60V, and The subsequent charging voltage is less than the initial charging voltage and greater than or equal to 4.45V.